Telemetry System for Transmission of Electrocardiographic Signals Uslng GSM - Wajahat Hussain (NUST Journal of Engineering Sciences, 2014)
Medical telemetry systems, also known as telemedicine, are evolving rapidly as wireless Communication technology advances, evidenced by the commercial products and research prototype for remote health monitoring that have appeared in recent years.